Analisis Berpikir Kreatif Siswa dalam Menyelesaikan Soal HOTS Materi Bangun Ruang Siswa SMP ditinjau dari Level Berpikir Van Hiele - Moh. Habil S. Saleh; Sukayasa; Mubarik; Pathuddin (Universitas Swadaya Gunung Djati, 2025)
This study aims to describe students' creative thinking abilities in solving HOTS geometry problems as viewed from Van Hiele's thinking levels. This study uses a qualitative descriptive approach with a method of analyzing the creative thinking process based on Van Hiele's thinking levels, which include: level 0 (visualization), level 1 (analysis), level 2 (informal deduction), level 3 (deduction), and level 4 (rigor). The research subjects consisted of three students: one at level 0, one at level 1, and one at level 2. The research subjects were selected based on the results of the VHGT test. Data collection techniques were conducted through the VHGT test, HOTS questions, and unstructured interviews, then analyzed using data condensation, data presentation, and conclusion/verification. The results of the study indicate that students' creative thinking levels are related to Van Hiele's thinking levels. The higher the Van Hiele thinking level of the students, the more complex and creative the problem-solving strategies used.